A NEW SPECIES OF BALANOPHORA FROM THE MALAY PENINSULA - GREGORI G. HAMBALI (Research Center for Biology, 1980)
An illustrated description of Balanophora hansenii Hambali, spec,nov. is presented. The species belongs to sect. Dibalaniella.